Description of two new species of Sinophlaeoba and the female of S. bannaensis (Orthoptera: Acrididae) from Yunnan, China - Mao, Ben-Yong; Ou, Xiao-Hong; Ren, Guo-Dong (Zootaxa, 2008)
The generic diagnosis of genus Sinophlaeoba Niu et Zheng, 2005 is reviewed. The main morphological characters that this genus distinguishes with its relatives are: head nearly as long as pronotum; pronotum with irregular and short carinae between median and lateral carinae; tegmina not surpassing beyond the middle of hind femora and touching each other in mid dorsal line. S. laoyinshan sp. nov. and S. brachyptera sp. nov. from Yunnan, China are described as new species, as well as the female of S. bannaensis Niu et Zheng, 2005 for the first time. All specimens are deposited in the College of Life Sciences and Chemistry, Dali University (CLDU), except that are mentioned otherwise. A key to three known species is given.